Predictors of postnatal mother-infant bonding: the role of antenatal bonding, maternal substance use and mental health - Rossen, L.; Hutchinson, D.; Wilson, J.; Burns, L.; Olsson, C.A.; Allsop, Steve; J Elliott, E.; Jacobs, S.; Macdonald, J.; Mattick, R. (Springer, 2016)
The emotional bond that a mother feels towards her baby is critical to social, emotional and cognitive development. Maternal health and wellbeing through pregnancy and antenatal bonding also play a key role in determining bonding postnatally, but the extent to which these relationships may be disrupted by poor mental health or substance use is unclear. This study aimed to examine the extent to which mother-fetal bonding, substance use and mental health through pregnancy predicted postnatal mother-infant bonding at 8 weeks. Participants were 372 women recruited from three metropolitan hospitals in Australia. Data was collected during trimesters one, two and three of pregnancy and 8 weeks postnatal using the Maternal Antenatal Attachment Scale (MAAS), Maternal Postnatal Attachment Scale (MPAS), the Edinburgh Antenatal and Postnatal Depression Scale (EPDS), the Depression and Anxiety Scales (DASS-21), frequency and quantity of substance use (caffeine, alcohol and tobacco) as well as a range of demographic and postnatal information. Higher antenatal bonding predicted higher postnatal bonding at all pregnancy time-points in a fully adjusted regression model. Maternal depressive symptoms in trimesters two and three and stress in trimester two were inversely related to poorer mother-infant bonding 8 weeks postnatally. This study extends previous work on the mother’s felt bond to her developing child by drawing on a large sample of women and documenting the pattern of this bond at three time points in pregnancy and at 8 weeks postnatally. Utilising multiple antenatal waves allowed precision in isolating the relationships in pregnancy and at key intervention points. Investigating methods to enhance bonding and intervene in pregnancy is needed. It is also important to assess maternal mental health through pregnancy.